White root rot disease suppression in rubber plant with microbial co-inoculants and silicon addition - Shabbir, Imran; Abd Samad, Mohd Yusoff; Othman, Radziah; Wong, Mui Yun; Sulaiman, Zulkefly; Md Jaafar, Noraini; Bukhari, Syed Asad Hussain (Elsevier, 2020)
White root rot disease caused by Rigidoporus microporus results in major economic loss to rubber plantation in all rubber growing countries including Malaysia. This glasshouse trial was conducted to explore the potential of single and co-inoculation of Enterobacter sp. UPMSSB7 and arbuscular mycorrhizal fungi (Glomus mosseae) with silicon for white root rot disease suppression and plant growth promotion of rubber seedlings. Plants were artificially infected with R. microporus using rubber wood blocks. The results revealed that co-inoculation with silicon significantly reduced the disease incidence and disease severity of foliar and root rot symptoms and also recorded the highest disease reduction compared to control after 24 weeks of artificial infection with R. microporus. The highest stem height, girth size, chlorophyll content, leaf area, shoot and root dry weight, root length, root volume and root surface area were achieved by co-inoculation with silicon. The co-inoculation with silicon also significantly improved silicon content in roots and shoots and leaf nutrient contents (N, P and K). The Enterobacter sp. population density, mycorrhizal spore density and root colonization were increased in co-inoculation with silicon treatment as compared to control and single inoculation treatments. From this study, it was concluded that co-inoculation of Enterobacter sp. and arbuscular mycorrhizal fungi with silicon had potential to suppress Rigidoporus microporus and improve plant growth of rubber seedlings under glasshouse conditions.